2017
DOI: 10.1002/2016ja023826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot anisotropic He+ ions on the growth and damping of electromagnetic ion cyclotron waves in the inner magnetosphere

Abstract: Physics of electromagnetic ion cyclotron (EMIC) waves is complicated by inclusion of heavy ions. In particular, He+ ions in the magnetosphere have long been considered to play important roles. Motivated by recent observations, we examine the effect of the inclusion of hot anisotropic He+ ions in addition to the usual hot anisotropic protons. We solve the kinetic dispersion relation for this examination and find the following results. First, inclusion of hot anisotropic He+ ions leads to the growth of EMIC wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…EMIC waves in H + and He + bands are thought to be excited by ring current ions with temperature-anisotropy velocity distributions ( e.g., Cornwall, 1965;Kennel & Petschek, 1966;Kozyra et al, 1984;Lee et al, 2017;Xue et al, 1993;Yuan et al, 2016), which has been verified by satellite observations (e.g., Min et al, 2015).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…EMIC waves in H + and He + bands are thought to be excited by ring current ions with temperature-anisotropy velocity distributions ( e.g., Cornwall, 1965;Kennel & Petschek, 1966;Kozyra et al, 1984;Lee et al, 2017;Xue et al, 1993;Yuan et al, 2016), which has been verified by satellite observations (e.g., Min et al, 2015).…”
Section: Introductionmentioning
confidence: 82%
“…EMIC waves in H + and He + bands are thought to be excited by ring current ions with temperature‐anisotropy velocity distributions ( e.g., Cornwall, ; Kennel & Petschek, ; Kozyra et al, ; Lee et al, ; Xue et al, ; Yuan et al, ), which has been verified by satellite observations (e.g., Min et al, ). Considering that EMIC waves in O + band have different properties in comparison with those in H + and He + bands, that is, O + band EMIC waves often have large wave normal angles and left‐hand or/and linear polarization (Saikin et al, ; Yu et al, ), Yu et al () have used linear growth theory to predict that O + band EMIC waves might be excited by protons with ring velocity distributions ( ∂f ⊥ / ∂v ⊥ > 0, where f ⊥ = f ( v ⊥ , v // = 0) is the perpendicular velocity distribution).…”
Section: Introductionmentioning
confidence: 88%
“…By assuming that the particle population can be described by bi‐Maxwellian distributions (Chen et al, ; Gary et al, ; Stix, ), the hot plasma dispersion relation of left‐hand parallel‐propagating EMIC waves in a multi‐ion plasma consisting of hot anisotropic protons and four cold particle species, that is, cold electrons, protons, He + ions, and O + ions, can be written as (e.g., Gary, ; Kozyra et al, ; Lee et al, ) lefttrue()italiccknormalΩ2=1ωpe2normalΩ1Ω+Ωe+ηcpεpΩnormalΩp+ηHe+εp4ΩnormalΩp+ηO+εp16ΩnormalΩpωpe2ηhpεpΩ2Ahp+Ahp+1ΩnormalΩp+normalΩpZζkαtrue‖. …”
Section: Methodsmentioning
confidence: 99%
“…However, the warm/hot (>1 keV) He + ions have been frequently observed during the EMIC emissions (Anderson & Fuselier, ; Young et al, ). In the presence of hot ions, the cold plasma approximation is invalid, and the kinetic effect of hot ions cannot be ignored (e.g., Chen et al, , ; Lee et al, ; Ni et al, ; Silin et al, ). Ni et al () considered the effect of hot protons on the electron pitch angle scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Ni et al () considered the effect of hot protons on the electron pitch angle scattering. Lee et al () suggested that anisotropic hot He + ions probably contribute to the growth of He + band EMIC waves in the high‐density plasmasphere or plume. However, the effect of hot He + ions on the electron pitch angle scattering driven by EMIC waves remains unknown.…”
Section: Introductionmentioning
confidence: 99%